Dynamics of international migration networks of Spaniards living abroad. - De-Miguel-Luken, Verónica; Recaño-Valverde, Joaquín (My University, 2023)
International migration flows can be conceptualized as valued directed networks with countries as nodes and the number of migrants from origin to destination as the tie weight. In this research, we model the international migration flows of Spaniards among 57 countries across the world between 2011 and 2021. However, the interest was about migration patterns between countries others than Spain, experienced by Spaniards many of whom might not have even been born or lived in Spain (acquired citizenship because of Spanish ancestors). Ordered SAOMs were run. In order to set this nested structure three different thresholds were used, according to different flow intensities (above 10 cases, above 50, and above 100). Preliminary results showed a significant positive tendency to reciprocity, transitivity and in-degree popularity, although indegree was not clearly significant for higher intensity migration networks. The negative outdegree coefficients across networks indicate that flows are relatively infrequent. The positive indegree popularity effect in low intensity networks points to the fact that countries with larger numbers of receiving ties tend to attract additional in-flows. The significant positive effect for transitivity together with the negative effect for 3-cycles suggest that it is more likely that main destinations are reached both through a third intermediate country or through a direct emigration, than return migration flows are observed from those destinations. Finally, and again for the low intensity migration networks, having English as an official language at destination increases the likelihood of receiving a flow, whilst Spanish as the main language in the sending country increases the likelihood of out-migration. The larger the number of Spaniards already living in the destination country the higher the likelihood of receiving a flow. Sharing border and language also show positive effects, together with the country’s GNI for the in-coming flows.
Keywords: Emigración e inmigración; Españoles; Emigrantes; Migraciones internacionales; Población española; Análisis de redes; Flujos